2008
DOI: 10.1128/aac.01361-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Strand Transfer That Prevent Integration and Inhibit Human T-Cell Leukemia Virus Type 1 Early Replication

Abstract: The replication of the retrovirus human T-cell leukemia virus type 1 (HTLV-1) is linked to the development of lymphoid malignancies and inflammatory diseases. Data from in vitro, ex vivo, and in vivo studies have revealed that no specific treatment can prevent or block HTLV-1 replication and therefore that there is no therapy for the prevention and/or treatment of HTLV-1-associated diseases in infected individuals. HTLV-1 and human immunodeficiency virus type 1 (HIV-1) integrases, the enzymes that specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…This study was conducted according to the principles outlined in the Declaration of Helsinki, and approved by the Institutional Review Board of the Hospices Civils de Lyon (France). As previously described [ 29 , 30 ], CD4 + clones were submitted to ex vivo culture for one month prior to HTLV-1 screening and RNA extraction. At this time, infected and uninfected cells remained non-immortalized and required IL-2 for continued growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was conducted according to the principles outlined in the Declaration of Helsinki, and approved by the Institutional Review Board of the Hospices Civils de Lyon (France). As previously described [ 29 , 30 ], CD4 + clones were submitted to ex vivo culture for one month prior to HTLV-1 screening and RNA extraction. At this time, infected and uninfected cells remained non-immortalized and required IL-2 for continued growth.…”
Section: Resultsmentioning
confidence: 99%
“…For T-cell limiting dilution cloning, PBMCs were seeded at 0.1 cell/well in Terasaki plates after removal of adherent cells. T-lymphocytes were cultured in RPMI 1640 containing penicillin and streptomycin, sodium pyruvate, non-essential amino acids, 2-mercaptoethanol, 10% filtered human AB serum, 100 U/mL recombinant IL-2 (Chiron Corporation), and 75 μM HTLV-1 integrase inhibitor L-731,988 [ 30 ]. T-lymphocytes were re-stimulated every 14 days with PHA (1 μg/mL) and fresh feeder cells (5.10 5 cells/mL) that were composed of lethally irradiated PBMCs from three distinct allogenic HTLV-1-negative donors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HTLV-1 transmission was performed by co-culturing the PBMCs with lethally irradiated (60 Gy) HTLV-1-positive MT2 cells at a ratio of 5:1, as described elsewhere [24]. The MT2 cell line is known to be chronically infected with HTLV-1 [25].…”
Section: Methodsmentioning
confidence: 99%
“…Infectivity of PFV in cell culture and in vitro enzymatic activities of PFV IN showed a significant sensitivity to raltgravir and elvitegravir [24]. The high degree of amino acid sequence similarity within the active sites of HIV-1 and PFV INs and superposition of active side residues in crystals [24] implies the possibility of HIV-1 IN strand transfer inhibitors to be equally active against PFV IN [24,105,106]. Soaking PFV intasome crystals in raltegravir or other INSTIs has revealed that these compounds bind the active site and are interacted by their oxygen atoms with bound metal ions at the IN active site [25].…”
Section: Structural Basis Of In Inhibitor Actionmentioning
confidence: 99%